ANALISIS KOMERSIALISASI PADA PRODUKTIVITAS LEMBAGA KEUANGAN MIKRO - Risang Surya Wibowo; Deny Dwi Hartomo (Riset Manajemen dan Akuntansi, 2015)
The purpose of this study is to examine the influence of commercialization, which is measured by variablessize of loan portfolio, return on equity, leverage, age of MFI, and women clientele on yield rate. The population is all of microfinance institutions in Indonesia registered on Microfinance Information Exchange for the period 2007–20012. Purposive sampling is used to choose the sample and 50 microfinance institutions are found to be sample for five years research. The researcher uses simple linear regression with SPSS 16.0 for Windows. The result shows size of loan portfolio, return on equity, leverage, age of MFI, and women clientele are simultaneously have positive and significant influence on yield rate. It shows that size of loan portfolio has negative and significant influence on yield ratein 10%, ROE has positive and significant influence on yield rate in 1%, age of MFI has negative and significant influence on yield rate in 1%.Leverage and women clientelehas negative butinsignificant influence on yield rate. Keywords : commercialization, yield rate, size of loan portfolio, return on equity, leverage, age of MFI, women clientele, microfinance institutions